Is the graduate attributes approach sufficient to develop work ready graduates? - Srivalli Vilapakkam Nagarajan; Jenny Edwards (Journal of Teaching and Learning for Graduate Employability, 2014)
Many universities have graduate attributes often referred to as generic skills, soft skills or work ready skills. Our study of the professional work experiences of recent Australian Information Technology (IT) graduates found that communication, time management, teamwork, working with people, working across cultures, project management and business skills are some of the major categories of professional skills IT graduates believe are required for their work. This paper describes the study details and findings which raise questions about the adequacy of the graduate attributes approach in the development of professional skills such as the ability of graduates to work across cultures and on multiple projects which are major requirements in many IT (and other) workplaces. IT graduates’ gave views on the challenges they face at work, the typical professional skills requirements of their practice and how they acquired or developed them, the elements of their university study that are relevant to their work professional skills requirements and how well their studies prepared them to meet the professional needs of their practice.